Forecasting the trend in cases of Ebola virus disease in West African countries using auto regressive integrated moving average models - M., Manikandan; A., Velavan; Singh, Zile; Purty, Anil J.; Bazroy, Joy; Kannan, Senthamarai (International Journal Of Community Medicine And Public Health, 2017)
Background: Ebola Virus Disease (EVD), formerly known as Ebola haemorrhagic fever, is a severe, often fatal illness in humans. The current outbreak in West African countries like Guinea, Liberia and Sierra Leone is one of the largest in the history. Hence, to forecast the trend in a number of cases of EVD reported in these Countries a univariate time series model was used. Methods:We adopted an Auto Regressive Integrated Moving Average (ARIMA) models on the data collected between March 2014 to December 2014 and verified it using the data available between Jan 2015 to June 2015. The same has been used to predict the number of cases till December 2016 without any additional intervention. Results: The results also showed an increasing trend in the actual and forecasted numbers of EVD cases. The appropriate ARIMA (1, 1, 0) model was selected based on Bayesian Information Criteria (BIC) values. Conclusions:Hence, to prevent the disease from getting established as an endemic in these countries, additional interventions with an increase in the intensity of existing interventions and support of the international community along with WHO is essential to stop the epidemic.